A case of testicular tumor associated with the contralateral undescended testis - Ueda, H (Hinyokika kiyo. Acta urologica Japonica, 1995)
A 36-year-old man visited the hospital complaining of painless swelling of the right scrotal contents. His left scrotal contents were absent in the scrotum. Right inguinal orchiectomy was performed on May 17, 1993 under the diagnosis of testicular tumor. The pathological diagnosis of the tumor was pure seminoma. Abdominal computed tomography (CT) and magnetic resonance imaging (MRI) revealed the enlargement of para-aortic lymph nodes and there was a soft tissue signal in the left inguinal region which seemed to be the left testis in MRI. His serum testosterone level was low and gonadotropin level was high. The left orchiopexy was performed on June 24, 1993, but the left testis was finally removed because of methicillin-resistant Staphylococcus aureus (MRSA) infections. Radiation therapy was done against the metastatic lesion in the retroperitoneal lymph nodes and complete remission was obtained. The left undescended testis pathologically showed atrophy of germ cells but there was no appearance of atypia of Leydig cells or germ cells